Noise reduction in quantum communication - Yap, Jiun Yan. (2013)
Spontaneous anti-Stokes Raman noise (SASRN) had been identified to cause performance degradation of a quantum key distribution (QKD) system. For a QKD system using 1550nm as classical channel and 1310nm for quantum channel, it will suffer from SASRN as the strong 1550nm signals will create broadband noise that overlaps with the 1310nm quantum channel, resulting in higher noise level in the quantum channel. Though SASRN is supposedly weak, it has a very strong impact on QKD systems as these systems are operating at single photon levels. This project aims to reduce the impact of SASRN on QKD systems through the use of a very narrow filter. However, the presence of long-term drift in the laser’s centered wavelength and filter’s pass-band will result in a mismatch between the signal’s wavelength and the band-pass of the filter. Therefore there is a need to stabilize the centered wavelength of both the laser source and the filter to ensure smooth communication. A power and wavelength stabilized laser source employing the wavelength locker method was implemented to allow narrow filtering. Laser’s wavelength was stabilized up to a standard deviation of approximately 5×〖10〗^(-4)nm.